"Tried and Trusted Patriots" for the CIA: Latvian Case Study of the KGB Operativnaia Igra Theory. Issue 1 (2nd January 2023) - Falkov, Yaacov
Abstract: In 1952–1957, Soviet counterintelligence launched operation METEOR in Latvia, reacquired by the USSR during World War II. Based on a wide net of double agents in the local anti-Soviet resistance, that clandestine enterprise aimed at convincing Washington to halt its intelligence and influence activities on Latvian soil. The Russian, Latvian, and Western sources have expressed varied, at times polarly opposed, assessments of METEOR's actual effectiveness. This article uses newly acquired relevant American and Soviet sources to create a balanced picture of the U.S.–Soviet clandestine encounter in Latvia in the 1950s. Especially highlighted is the implementation on Latvian soil of the Soviet theory of strategic counterintelligence and deception operations based on double agents. Encouraged by its ability to recover METEOR's principal stages—successful evolvement, efficacy's zenith, and subsequent decline—the article proposes future theoretical inquiry into the paradoxical logic of intelligence and counterintelligence victorious operations and particularly into the notion of those operations' "culmination points."